Private Investment in Large Transport Projects Increases during the First Semester of 2011, Concentrated in India and the Road Sector - Nicholas, Alexander (World Bank, Washington, DC, 2013)
In the first semester of 2011, 34 new transport projects with private participation reached financial or contractual closure in nine low- and middle-income countries, involving investment commitments (hereafter investments) of US$17 billion.1 Investment in the first semester of 2011 increased by 17 percent compared with the first semester of 2010, on par with pre-crisis levels in the first semester of 2008. By number of projects, activity in 2011 decreased by 31 percent compared with the first semester of 2010 indicating fewer, larger projects in middle income countries. As in recent periods, private investment continued to concentrate in India and the road sector globally. India attracted 70 percent of private investment in transport and implemented 65 percent of transport projects with private participation. Globally, there were 23 road projects involving investment of US$8.7 billion. Railroads attracted the second highest investment level with US$6.1 billion invested in three large metro transit projects. Five port projects reached financial closure with investments of US$1.4 billion, and three airport projects attracted investments of US$360 million.